Human leukocyte antigen - HLA B*27: Unraveling the link to pathogenesis - Sakir Ahmed; Ramnath Misra (Indian Journal of Rheumatology)
The association of spondyloarthritis (SpA) with human leukocyte antigen-B*27 (HLA-B*27) is one of the strongest known for a non-monogenic disease. How HLA-B*27 determines the aetiopathogenesis of SpA and disposes toward this group of disease has perplexed rheumatologists for decades. We searched through contemporary bibliographic databases for literature on the link between HLA-B*27 and different SpA, with special emphasis on ankylosing spondylitis. In this review, the structure and function relationship and subtypes of HLA-B*27 are discussed in the context. Then, three hypotheses on the pathological role of HLA-B*27 are presented. The first arthritogenic peptide hypothesis is based on molecular mimicry between the parts of the HLA-B*27 and epitopes of pathogenic Enterobacteriaceae. The second hypothesis is about the misfolding of the HLA-B*27 major chain, leading to endoplasmic reticulum (ER) stress and initiation of inflammation through the unfolded protein response. The third hypothesis deals with the formation of homodimers of the HLA-B*27 major chain on the cell surface, leading to the activation of natural-killer cells through the killer immunoglobulin-like receptors. Furthermore, discussed in the review are the epistatic factors such as ER-associated peptidase-1, role of microbiota, and the concept of autoinflammation in relation to HLA-B*27.